Battered Woman Syndrome, Diminished Responsibility and Women Who Kill: Insights from Scottish Case Law. (October 2019) - McPherson, Rachel
Using Scotland as a case study, this article maps the development of Battered Woman Syndrome in law. It looks to the potential space for development that has been created by the recent case of Graham v HM Advocate, concluding that such a more would be an important step and one with significant implications for domestic abuse policy and the treatment of female accused more widely.